Draft Genome Sequence of Bacillus thuringiensis Strain UNMSM10RA, Isolated from Potato Crop Soil in Peru - Delgado Silva, Yolanda Bedsabé (2020)
The 5.5-Mb genome sequence of Bacillus thuringiensis strain UNMSM10RA, isolated from potato crop soil, is reported in this study. The strain UNMSM10RA contains 5,347 protein-coding sequences, 105 tRNA genes, 15 rRNA genes, and 5 noncoding RNA (ncRNA) genes, with an average G+C content of 35.1%. Within protein-coding genes, 31 were detected and identified in the metabolism of heavy metals such as arsenic, cadmium, and copper. Further analyses will be performed and provide more information for understanding the evolution of these Bacillus thuringiensis strains and their potential uses.